2015
DOI: 10.3748/wjg.v21.i4.1268
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of early gastric cancer using narrow band imaging and acetic acid

Abstract: A combination of NBI-ME and EME was useful in predicting the histological type of depressed-type EGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, no studies have reported the difference between EGCs of the corpus and antrum under ME-NBI. The MV and MS features of EGC summarized in previous studies also cannot be used to distinguish between the different regions of antrum and corpus [13,[15][16][17][18]. We hypothesize that there may be different MV and MS patterns between EGCs of the corpus and antrum under ME-NBI.…”
Section: Introductionmentioning
confidence: 81%
“…However, no studies have reported the difference between EGCs of the corpus and antrum under ME-NBI. The MV and MS features of EGC summarized in previous studies also cannot be used to distinguish between the different regions of antrum and corpus [13,[15][16][17][18]. We hypothesize that there may be different MV and MS patterns between EGCs of the corpus and antrum under ME-NBI.…”
Section: Introductionmentioning
confidence: 81%
“…A study using iScan for the detection of pre-cancerous or early cancerous lesions within the stomach found that, although imaging quality was improved, there was little additional diagnostic benefit 4 . However, recently Matsuo et al found that using magnifying endoscopy with NBI (enhanced by the application of acetic acid) aided the diagnosis of early gastric cancers 7 . Similarly, a study by Dohi et al found that using BLI increased the detection of early gastric cancer with an accuracy, sensitivity, and specificity of 90.7, 84.6 and 92.4%, respectively, compared to 72.9, 30.8 and 84.8% using high-definition white light alone 8 .…”
Section: Advances In Digital Imagingmentioning
confidence: 99%